Erosão urbana na bacia do córrego Santo Antônio em Aparecida de Goiânia/Goiás: análise e diretrizes para controle - Oliveira, Carlos José Ferreira de (2005)
The municipal district of Aparecida of Goiânia contains the second most important city of the State of Goiás. It embraces 292Km2 approximately and has a population of approximately 336.392 inhabitants (Census 2000, IBGE). Due to the conurbation with the capital of the State, Aparecida has been registering, mainly for the last 20 years, an intense urbanization associated to the economical and industrial growth, as a result of the process of expansion of the city of Goiânia, which has resulted in a fast, intensive and disordered occupation of the urban land, by people coming from several parts of the state, and from other regions of the country, in search of work and better life conditions. The micro-basin of the Córrego Santo Antônio, with approximately 157,39 Km2, represents 53,90% of the total area of the municipal district, contains practically the whole urban area, possesses a larger density of drainage channels and presents the largest number of negative environmental impacts of the whole municipal district. In that area, among those impacts, the occurrence of 60 lineal erosive occurrences (ravines and “boçorocas” - this last word is spelled “ibi-çoroc” and means “torn earth” in Tupi-Guarani, a Brazilian indigenous language) of spiritual medium and big sizes were verified, which have caused socioeconomic damages to the city hall and the population, and have changed the environmental quality of the municipal district. For that reason, the theme urban erosion and that particular micro-basin have been chosen for this study aimed at investigating the different types and distribution of the lineal erosive features and their relationships with the conditionings of the physical environment, mainly the use and occupation, and the readiness of urban infrastructure, so as to look for the understanding of their causes and consequences, with a view to subsidize the control actions. In order to reach the proposed objective, it was implemented successive phases of studies, starting by the compilation of existent cartographic material on the components of the physical environments, treaties of an including scale, followed by analysis of aerial pictures and of the satellite image Landsat ETM 7 + (2003), in detail scale. Subsequent integration of the data to delimit the homogeneous units and the forms of use and occupation capable and possible of the erosive phenomenon, besides detailed study, in loco, of the most representative focuses were made. Finally, by the integrated analysis of data, through crossing techniques, synthesis letters related to the susceptibility and risk to the lineal erosion were elaborated, which gave support to the conclusive interpretations and the proposition of preventive measures of control that can be integrated into the urban master plan that has just been completed. The conclusion is that most of the erosive focuses is of the ravine type, caused by the concentration of superficial water flows, in areas naturally susceptible, where it was also verified: lack or inadequacy of urban infrastructure, mainly with respect to micro-drainage net; impermeability of the urban soil associated to the growing rates of construction, paving, and inadequacy of infiltration areas such as gardens and public parks; plan and inadequate position of lots; lack or inadequacy of appropriate technical support and/or of funds for preventive and corrective control of the phenomenon. Such factors were related to the absence or inadequacy of public policies for the well being of the population, in a long run, as it happens in countless Brazilian cities, whose origin emanate from decisions made at national level, mainly over the last four decades, as a result of the said "developmental political model”.